Moral Values in Mandailing Song Lyrics by Top Simamora feat Dealiana Lubis - Pahutar, Lenni Juliani; Tangkas, I Wayan Dirgeyasa (Universitas Negeri Medan, 2021)
The objectives of this study were to find out meanings, what, how, and why he author conveys moral values through the lyrics of the song Mandailing by Top Simamora based on social life. This study was conducted using an descriptive qualitative method. The data of this study were taken from Mandailing song lyrics by Top Simamora Feat Deliana Lubis. The sources of the data were ;˜Nantulang Manyuru Sirang™, ˜Pasikolahon™, ˜Gagal Maroban Boru™, ˜Boru Na Beteng™, ˜Caleg Na Tuppur™, ˜Titik Sapartambuan™, ˜Biaso Pe™, ˜Nasibku Marboru™, ˜Gut-gut Rap Sombong™, ˜Rumah sakit Panyosalan™. The data were analyzed by using Kinnear™s theory. The writer found there were four types of moral values namely, commitment to something greater than oneself (26.2%), self-respect but with humbleness or respect to others, self-discipline, and acceptance of personal responsibility (33.3%), respect and caring for others (14.3%) and faith (26.2%). 2) Moral values were realized verbally. 3) There were some reasons author conveys moral values through Mandailing song lyrics by Top Simamora feat Deliana Lubis such as inspired by the realities of the life problems of Mandailing™s society, as a medium to convey advice without satirize the others, to make people or society aware , and to motivate the listeners do kindness.